2009
DOI: 10.3168/jds.2008-1281
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for major milk proteins in Dutch Holstein-Friesians

Abstract: The objective of this study was to estimate genetic parameters for major milk proteins. One morning milk sample was collected from 1,940 first-parity Holstein-Friesian cows in February or March 2005. Each sample was analyzed with capillary zone electrophoresis to determine the relative concentrations of the 6 major milk proteins. The results show that there is considerable genetic variation in milk protein composition. The intraherd heritabilities for the relative protein concentrations were high and ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
108
13
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(169 citation statements)
references
References 28 publications
40
108
13
8
Order By: Relevance
“…It has been found in the present study that the content of protein is rather constant throughout the seasons. This agrees with other studies that have shown that protein composition is influence by feeding practices only to a small extend ( Schopen et al, 2009;Heck et al, 2009;Coulon et al, 1998;Ozrenk and Selcuk Inci, 2008).…”
Section: Introductionsupporting
confidence: 93%
“…It has been found in the present study that the content of protein is rather constant throughout the seasons. This agrees with other studies that have shown that protein composition is influence by feeding practices only to a small extend ( Schopen et al, 2009;Heck et al, 2009;Coulon et al, 1998;Ozrenk and Selcuk Inci, 2008).…”
Section: Introductionsupporting
confidence: 93%
“…Heritability estimates for the six major milk proteins range from 0.25 to 0.80 (Schopen et al, 2009;Bonfatti et al, 2011). Heritability estimates from both studies differ for certain milk proteins, especially for b-casein and b-lactoglobulin, which might be because of differences in the methods used to quantify the milk proteins (capillary zone electrophoresis v. HPLC).…”
Section: Heritabilities and Genetic Correlationsmentioning
confidence: 96%
“…Recent studies demonstrate that milk protein composition is strongly affected by genetic factors (Schopen et al, 2009;Bonfatti et al, 2011). Heritability estimates for the six major milk proteins range from 0.25 to 0.80 (Schopen et al, 2009;Bonfatti et al, 2011).…”
Section: Heritabilities and Genetic Correlationsmentioning
confidence: 99%
“…The main technological value of milk was characterised by casein ratio, according to application of the standards of the Center of Chemical Patterns in Italy and Foss, and also, by the casein number and casein index (Schopen et al 2009). …”
Section: Animals and Dietsmentioning
confidence: 99%